Digital technology advancements in knowledge management - Gyamfi, Albert, 1974-; Williams, Idongesit (Advances in knowledge acquisition, transfer, and management (AKATM) book series, 2021)
"This book discusses and addresses how various new and emerging digital technologies either can or currently support Knowledge Management processes within organizations by offering case studies and practical tips based on research on the emerging possibilities for knowledge management using these technologies"--